A Real Model of Transitional Growth and Competitiveness in China - Lipschitz, Leslie; Rochon, Celine; Verdier, Genevieve (Washington, D.C. : International Monetary Fund, 2008)
We present a stylized real model of the Chinese economy with the objective of explaining two features: (1) domestic production is highly competitive in the sense that an accumulation of capital that raises the marginal product of labor elicits increases in employment and output rather than only in wages; and (2) even though the domestic saving rate is high, foreign direct investment is also substantial. We explain these features in terms of a conventional neoclassical growth model-with no monetary or nominal exchange rate policy-by including two aspects of the economy explicitly in the model: (1) low production wages are sustained by a large reserve army of rural labor which drives internal migration, and (2) domestic capital is distinct from importable capital and complementary with it in production. The results suggest that underlying real phenomena are important in explaining recent history; while nominal renmimbi appreciation may dampen price and wage increases, it would probably not change the real factors that have sustained rapid growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet